Hemoglobin concentration is correlated with Low Birth Weight Babies (LBWB) - Ratna Ningsih; Fitri Febriana (Journal of Health Technology Assessment in Midwifery, 2019)
Out of 9% prevalence of Low Birth Weight Babies (LBWB), 5.32% takes place in Special Region of Yogyakarta. Out of 5 municipalities in Yogyakarta, the highest rate of LBWB case takes place in the Municipality of Kulon Progo. According to perinatal birth rate in Kulon Progo in 2018, out of 2,392 babies, 359 babies were born with LBWB. Babies born with LBWB condition may experience breathing pattern problem, hypothermia and other potential infections. The population of this study were 2,392 babies delivered in a Public Hospital within the Municipality of Kulon Progo, Yogyakarta City in the period of January-December 2018. Mothers giving birth to 171 babies with LBWB condition (50%) and 171 babies of normal birth weight (50%). Respondents' characteristic determined in the study is those with the risk factor of Hemoglobin (Hb) concentration of 44.7%. According to the analysis result, hemoglobin concentration correlates with the case of LBWB with p-value of 0,000 and Odd Ratio of 7.638 times.